2012
DOI: 10.1590/s0100-736x2012000300001
|View full text |Cite
|
Sign up to set email alerts
|

Causes of death of thoroughbred racehorses at Octavio Dupont Veterinary Hospital, Brazilian Jockey Club, Rio de Janeiro

Abstract: There are few studies that approach the epidemiology of deaths in racehorses in a broad manner. The majority focus on a specific affection or procedure. Brazil does not have a program instituted for the monitoring of deaths of horses. By means of a descriptive study in association with a multivariate analysis method, an epidemiologic profile was determined for deaths related to musculoskeletal (MS), gastrointestinal (GI), respiratory (RES) systems, neurologic origin (NEU) and sudden death (SD) for the years of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…Although rare, the use of multivariate statistical techniques in veterinary medicine allows the study of the interdependence between the variables of each horse, making it possible to raise specifi c and accurate questions of considerable complexity, in a set of data, turning m-dimensional information into tri or bi-dimensional (MANLY, 2008;PEREIRA et al, 2012). Multivariate correspondence analysis using the techniques of perceptual and intuitive representations (HAIR, 1995) was extremely important to show the relative similarities or preferences in relation to categories of variables studied.…”
Section: Discussionmentioning
confidence: 99%
“…Although rare, the use of multivariate statistical techniques in veterinary medicine allows the study of the interdependence between the variables of each horse, making it possible to raise specifi c and accurate questions of considerable complexity, in a set of data, turning m-dimensional information into tri or bi-dimensional (MANLY, 2008;PEREIRA et al, 2012). Multivariate correspondence analysis using the techniques of perceptual and intuitive representations (HAIR, 1995) was extremely important to show the relative similarities or preferences in relation to categories of variables studied.…”
Section: Discussionmentioning
confidence: 99%
“…Knowledge of diseases that occur in the equine species is crucial for determining its economic importance as well as the establishment of control procedures. Numerous studies described the causes of death in horses in the United States (USDA 2017), Europe (Baker & Ellis 1981) and Brazil (Pierezan et al 2009, Pereira et al 2012, Marcolongo-Pereira et al 2014. In these studies, the alimentary and locomotor systems were the most commonly affected (Baker & Ellis 1981, Pierezan et al 2009, Pereira et al 2012, USDA 2017, while the respiratory system has been indicated as one of the five leading causes of death in horses (Baker & Ellis 1981, Pierezan et al 2009, Pereira et al 2012, USDA 2017.…”
Section: Introductionmentioning
confidence: 99%